Application of the Law to Criminal Perpetrators who Jointly Commit the Crime of Premeditated Murder (Case Study of North Jakarta District Court Decision Number 213/Pid.B/2021/Pn.Jkt.Utr) - Kusumoyudo, Bayu; Ajie, Bintang Wicaksono (LITERATUS, 2024)
The crime of murder is a form of crime in a person's soul where the act is very contrary to the norms that exist in society, namely religious norms and customs, as well as contrary to the norms of criminal law provisions and violates human rights, namely the right to life. The formulation in this study is how the application of the law to perpetrators of criminal acts together committing premeditated murder according to the Criminal Code and how to analyze the basic considerations of the North Jakarta District Court judge in issuing a verdict number 213 / Pid.B / 2021 / PN.Jkt.Utr. The research method used is normative juridical, namely library legal research carried out by examining library materials or secondary data. The results of the study show that the crime of premeditated murder in Article 340 of the Criminal Code is an act of murder carried out with prior planning. The requirements for stating that the element of prior planning has been fulfilled are: First, deciding the will calmly. Then, there is sufficient time from the emergence of the will to the implementation of the will. Then the implementation of the will (action) in a calm atmosphere. In decision number 213/Pid.B/2021/PN.Jkt.Utr the Judge opined that the defendant was found guilty and the judge sentenced the Defendant to 10 (ten) years in prison. According to the author, the criminal sanctions imposed by the Judge were much lighter than the demands of the public prosecutor for 18 years. In addition, the judge's decision was not in accordance with the retributive nature of the punishment. Referring to pArticle 340 of the Criminal Code states that the threat to perpetrators of premeditated murder is the death penalty or life imprisonment or a certain period of time, a maximum of twenty years.. Keywords: Implementation of law, Premeditated murder, judge's decision